PENGARUH PIJAT BAYI TERHADAP POLA TIDUR BAYI USIA 0-6 BULAN - Happy Marthalena Simanungkalit (MMJ (Mahakam Midwifery Journal), 2019)
Based on WHO 2012 data included in the journal Pediatrics, there were around 33% of infants experiencing sleep problems. One of the causes of sleep problems is in fact a parent's mistake in putting the child to sleep. Healthy sleep habits should be implanted from infancy. Objective of this research to determine the effect of massage on the sleep patterns of infants aged 0-6 months. This study used atype study Quasi Experiment with adesign non equilaventwith control group design. The research was conducted from January to March 2018. The population of this study was balyi aged 0-6 months in the work area of ​​Terwan Health Center. The sample is 11 respondents. Data analysis using Chi Square. Based on the results of a statistical test, it was shown that 9 respondents (81.8%) had a massage, sleep patterns were not disturbed. Infants who were not massaged were 3 respondents (27.3%), sleep patterns were not disturbed. Chi square statistic test shows the value of P-Value 0.032 (P-Value<α 0.05) which means there are significant differences. Keywords: massaage, sleep patterns.